PENGARUH KUALITAS APLIKASI DAN KEAMANAN BERTRANSAKSI TERHADAP KEPUTUSAN PEMBELIAN E-COMMERCE SHOPEE DI MAHASISWA FKIP UNIVERSITAS RIAU - Meilititha Zulistiana; Suarman Suarman; Hardisem Syabrus (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This study aims to determine the effect of application quality andtransaction security on consumer purchasing decisions of e-Commerse shopee at FKIP,Riau University. The population in this study were students from FKIP, Riau Universitywho made purchases through the e-Commerse shopee application. This number cannotbe determined. The sampling technique uses the snowball sampling method, which is away to identify, select and take samples in a continuous network or chain of relationshipsuntil the number of samples in this study is 100 respondents. The data analysis used isthe prerequisite test that has been carried out by the SPSS Statistics Version 22 program.The results of the study state that 1) Application Quality has a positive andsignificant effect on Purchasing Decisions, 2) Transaction Security has a positive andsignificant effect on Purchasing Decisions, 3) Application Quality and TransactionSecurity have a positive and significant effect on Purchasing Decisions.Key Words: Application Quality, Transaction Security and Purchase Decisions